Changes in the Thermal and Hydraulic Regime within the Active Layer in the Qinghai-Tibet Plateau - XIE Changwei; ZHAO Lin; WU Tonghua; DONG Xicheng (Journal of Mountain Science, 2012)
The change trends of air temperature, precipitation and evaporation from 1999 to 2008 shows that the climate in the Qinghai-Tibet Plateau permafrost region had become warmer. The analysis of the systematic active-layer data monitoring network along the Qinghai-Tibet Highway indicated that the active-layer thickness had been increasing and the soil temperature was rising. The soil temperature was rising in winter but not at the end of spring or during the entire summer. With thickening and warming of the active layer, the liquid water content of the active layer had an obvious downward migration and liquid water content in the top horizons decreased, but in the deeper horizons it increased.